Inhibitors of aldehyde dehydrogenases of the 1A subfamily as putative anticancer agents: Kinetic characterization and effect on human cancer cells. (1st June 2019) - Jiménez, Rafael; Pequerul, Raquel; Amor, Adrián; Lorenzo, Julia; Metwally, Kamel; Avilés, Francesc Xavier; Parés, Xavier; Farrés, Jaume
Abstract: Aldehyde dehydrogenases (ALDHs) are enzymes catalyzing the NAD(P) + -dependent oxidation of aldehydes to their corresponding carboxylic acids. High ALDH activity has been related to some important features of cancer stem cells. ALDH1A enzymes, involved in the retinoic acid signaling pathway, are promising drug targets for cancer therapy, and the design of selective ALDH1A inhibitors has a growing pharmacological interest. In the present work, two already known compounds (DEAB and WIN 18, 446) and novel thiazolidinedione and pyrimido quinoline acetic acid derivatives (compounds5a and64, formerly described as aldo-keto reductase inhibitors) were tested as inhibitors of the ALDH1A enzymes (namely, ALDH1A1, ALDH1A2 and ALDH1A3) as a first step to develop some potential drugs for cancer therapy. The inhibitory capacity of these compounds against the ALDH1A activity was characterized in vitro by using purified recombinant proteins. The IC50 values of each compound were determined indicating that the most potent inhibitors against ALDH1A1, ALDH1A2 and ALDH1A3 were DEAB, WIN 18, 446 and compound64, respectively. Type of inhibition and Ki values were determined for DEAB against ALDH1A1 (competitive, Ki  = 0.13 μM) and compound64 against ALDH1A3 (non-competitive, Ki  = 1.77 μM). The effect of these inhibitors on A549 human lung cancer cell viability was assessed, being compound64 the only inhibitor showing an important reduction of cell survival. We also tested the effect of the ALDH substrate, retinaldehyde, which was cytotoxic above 10 μM. This toxicity was enhanced in the presence of DEAB. Both DEAB and compound64 were able to inhibit the ALDH1A activity in A549 cells. The current work suggests that, by blocking ALDH activity, drug inactivation may be avoided. Thus these results may be relevant to design novel combination therapies to fight cancer cell chemoresistance, using both enzyme inhibitors and chemotherapeutic agents. Highlights: Four compounds were tested in vitro and in cellula as inhibitors of ALDH1A enzymes. DEAB was a selective and competitive ALDH1A1 inhibitor in the nanomolar range. WIN 18, 446 was a selective and irreversible ALDH1A2 inhibitor. A thiazolidinedione derivative was the most potent non-competitive ALDH1A3 inhibitor. Retinaldehyde had a toxic effect on A549 cells which was enhanced by DEAB cotreatment.